The agrarian history of Sweden : 4000 BC to AD 2000 - Myrdal, Janken, 1949-; Morell, Mats (Nordic Academic Press, 2011)
Comprehensive and concise, this account details the agrarian history of Sweden, as it is defined by its present national borders, from the Neolithic times to present day. Key historical concepts and events are discussed, including the introduction of planned agriculture alongside the domestication of animals; the feudal relationships and interactions between men and women, various age groups, and different social classes during the Middle Ages; the changes brought about by industrialism and the development of political democracy; the effects of World Wars I and II; and Sweden's inclusion in the European Union in 1995. This study also examines the interdependence between agriculture and other industries as well as the relationship between agriculture and politics on a local, regional, national, and international level.